Gambaran Pengetahuan Pubertas pada Anak Usia Sekolah di SD Negeri 8 Tondano - Pangajouw, Christine Natalie; Oroh, Wenda; Renteng, Septriani (Mapalus Nursing Science Journal, 2023)
Background: elementary school children are categorized as pre-adolescence. At the end of school age, children will soon face puberty. Puberty is a time of change, both physical changes that occur quickly and psychological changes that can trigger deviant behavior if a child lacks preparation for puberty, even during puberty itself. The lack of knowledge about puberty is one of the causes of deviant behavior in that period. Purpose: this study is to describe the knowledge of puberty in elementary school children at Elementary School 8th Tondano. Research method: the research method that was used in this research is descriptive research design with a survey method, namely by using a puberty knowledge questionnaire totaling 20 questions. The sampling technique used was stratified random sampling, with a total sample of 116 students. Results: 66 respondents (56.9%) had good knowledge regarding puberty and 50 respondents (43.1%) had poor knowledge regarding puberty. Discussion: an overview of puberty knowledge in elementary school children in terms of the characteristics of the respondents such as age, gender, class, source of puberty knowledge, and education of the respondent's parents. Conclusion: the majority of respondents had good knowledge regarding puberty. Viewing from the characteristics in this study, respondents who had good knowledge regarding puberty were dominated by respondents aged 11 years, female respondents, class VI respondents, respondents who had parents with education level of high school, and respondents whose source of puberty knowledge from school.